The Multifaceted Pathways Linking Populism to Ethnic Minority Health; Comment on "A Scoping Review of Populist Radical Right Parties' Influence on Welfare Policy and its Implications for Population Health in Europe" - Karien Stronks; Charles Agyemang (Kerman University of Medical Sciences, 2021)
Based on a scoping review of empirical studies accompanied by interviews with experts, Rinaldi and Bekker studied the impact of populist radical right (PRR) parties on access to welfare provisions - the latter standing proxy for population health and for health inequalities in particular. We argue that populism can impact on migrant and ethnic minority health in multiple ways, in addition to the welfare mechanism specified in that review. These include institutionalised discrimination affecting individuals' positions in the social hierarchy, experiences of discrimination in interpersonal relationships, and a weakened legitimacy of health policies. Interdisciplinary teams that include public health scholars and political scientists should take up the challenge of understanding migrant and ethnic minority health from a systems perspective.